2020
DOI: 10.1177/2032284420946105
|View full text |Cite
|
Sign up to set email alerts
|

Exploring mutual trust through the lens of an executing judicial authority: The practice of the Court of Amsterdam in EAW proceedings

Abstract: In the groundbreaking decision Aranyosi and Căldăraru, the Court of Justice of the European Union (CJEU) recognised that in exceptional circumstances, the risk of a possible breach of the right not to suffer inhuman or degrading treatments may qualify as a ground to suspend a European arrest warrant (EAW) and, ultimately, bring the surrender procedure to an end. In this judgment (and in the subsequent decision in LM, dealing with the right to a fair trial), the Court has devised a two-tier test to assess the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In the Aranyosi & Căldăraru, LM and L and P cases, the CJEU developed and introduced cumbersome and involved two-step tests to evaluate whether flagrant breaches of fundamental rights occur in the context of detention circumstances and effective judicial protection. 86 First, it is necessary to collect reliable, specific and properly updated material indicating a systemic and generalised risk to fundamental rights, 87 which may require entering into dialogue with the issuing authorities. 88 Second, judicial authorities must be able to use this material to determine specifically and precisely whether there are substantial grounds that the requested person in concreto runs the risk of such a fundamental rights breach after surrender, 89 which places the onerous task on issuing authorities of assessing local situations on the ground in a different country.…”
Section: Discussionmentioning
confidence: 99%
“…In the Aranyosi & Căldăraru, LM and L and P cases, the CJEU developed and introduced cumbersome and involved two-step tests to evaluate whether flagrant breaches of fundamental rights occur in the context of detention circumstances and effective judicial protection. 86 First, it is necessary to collect reliable, specific and properly updated material indicating a systemic and generalised risk to fundamental rights, 87 which may require entering into dialogue with the issuing authorities. 88 Second, judicial authorities must be able to use this material to determine specifically and precisely whether there are substantial grounds that the requested person in concreto runs the risk of such a fundamental rights breach after surrender, 89 which places the onerous task on issuing authorities of assessing local situations on the ground in a different country.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of the practice of the Court of Amsterdam in EAW proceedings concluded that this court used the discretion that the CJEU's case law left to the executing authorities to shift emphasis from mutual trust to the fundamental rights of requested persons. 60 The ECtHR does not find this to be the decisive element; instead, it considers that since national courts have to follow the CJEU's case law closely when it comes to how the assessment is to be done (the two-step test) they ultimately do not enjoy any discretion. In practice, however, judicial discretion is usually a matter of degree that may be perceived and exercised differently by different judges and national courts, as also illustrated in the case law.…”
Section: Rebutting the Presumptionmentioning
confidence: 99%
“…If a risk exists that the requested person's right to a fair trial may be infringed, the EAW must be postponed and can eventually be annulled. 845 A central topic in the judgement is the independence of the judiciary. In the Court's view, the requirement of judicial independence is part of the essence of the fundamental right to a fair trial.…”
Section: An External Perspective -The Dutch Contribution To the Eu Ju...mentioning
confidence: 99%
“…The LM judgment was at issue in a number of cases before the Amsterdam District Court. 861 The Court took leading decisions on 16 August 2018 862 and 4 October 2018, 863 by which surrenders to Poland were suspended for the time being. In July 2020, the Court decided to refer two EAW cases to the CJEU, seeking clarification of the CJEU's approach in LM in the light of recent developments involving the deterioration of rule of law in Poland.…”
Section: � National Court Judicial Dialoguementioning
confidence: 99%